A CASE OF SEVERE THERMAL AND CHEMICAL BURN CAUSED BY AIRBAG DEPLOYMENT - Metodi Goshev; Ilina Brajnova-Michich; Atanas Christov; Biliana Mileva; Teodora Kiryakova; Alexander Alexandrov (Science & Research)

(untitled)
Introduction: Airbags significantly reduces mortality and morbidity in motor vehicle crashes. However, the airbag produces its own range of injuries. These are usually minor ones, but in certain circumstances they could be severe or even fatal. This is a case report of a serious hand burn of a driver after airbag deployment in a moderate frontal collision. Materials and methods: Full forensic examination, including analyses of medical documentation, inspection of photos from the early stages of the injury and series of examination of the injured person. Case Presentation: In order to escape a hurdle a driver lost control over his automobile and hit frontally a tree next to the road. The airbag opened due to the crush. Right after the accident, the driver saw that his left wrist was edematous and inflamed, with formation of blisters. The medical examination established 3rd degree burn in the area. During one month of special therapy the status of the patient was studied by our team and more burns of 2nd degree on the right forearm and the front right surface of the neck were established. Discussion: The analysis of the morphological findings, compared to the present knowledge of the airbag’s set-up, led to the conclusion that the injury was due to combined mechanical, thermal, and chemical action. The injury of the wrist cannot be taken as an acceptable or ordinary one for the airbag. It is probably a result of a defect of the activated airbag module. Conclusion: The present case is an indicator for the fact that one can never be 100% sure of “safety” of the car safety system, until an accident happens.